STRIKING A BALANCE BETWEEN SOCIAL COSTS AND SOCIAL BENEFITS OF INTELLECTUAL PROPERTY RIGHTS - Kaushal, Ishita (JIPRO: Journal of Intellectual Property, 2023)
This study underscores the need to reevaluate traditional IP paradigms and explore alternative models that strike a better balance between the resultant social costs and benefits. These alternatives encompass a range of strategies, including copyleft principles, trade secrets, etc., each offering unique pathways to mitigate social costs while preserving incentives for creativity. This research contributes valuable insights to the ongoing discourse on reshaping IP frameworks to create a more harmonious and sustainable environment that nurtures innovation and creativity while minimizing unintended societal repercussions.